Space-time coordination dynamics in basketball: Investigating the interaction between the two teams - Bourbousson, J.; Seve, C.; McGarry, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Bourbousson, Seve and McGarry (submitted) reported an investigation of space-time patterns of basketball players in terms of the couplings among player dyads. The present study examined basketball game behaviour from analysis of the interaction between the two teams, addressing whether basketball subscribes to dynamical system descriptions at different levels of analysis. Methods Six game sequences were selected for analysis from which the x-y coordinate data of each player was obtained. From these data the longitudinal and lateral movements of the teams were then analyzed using two metrics, the centre of gravity and the stretch index. The former assesses the central position of a team and the latter the dispersion of a team about its central position. The relative phase between the centres of gravity, as well as the stretch indexes, and a new measure termed the differential stretch index (i.e., the difference between the stretch indexes of the two teams) were then used as collective variables to assess the interaction between the teams. Investigation of correspondences between game events (i.e. shot attempts and ball possession) and the collective variables used was realized. Results In regard to the phase analyses, an in-phase relation between the teams was evidenced with more stability reported for the longitudinal direction than for the lateral one. The differential stretch index in contrast demonstrated two separate and stable properties for both the longitudinal (-0.6 m and 0.8 m) and lateral directions (-0.4 m and 0.6 m). In the investigation of correspondence between game events and collective variables, qualitative analyses identified two classifications of shot attempts: individual shots and team shots, with the second shot type being produced seemingly just after a large perturbation in relative phase between centres of gravity when measured in the lateral direction. Major variations in the differential stretch index were related with changes in ball possession. Discussion The different results obtained by using different metrics and collective variables demonstrate that the information obtained from the analysis is much informed by the particular indicator used. The relative phase perturbations of the centres of gravity were forecasting shot attempts when produced by team work. This indicator might well contain useful information for sports practitioners. Otherwise, the supposition that in general the attacking team tends to expand and the defending team contracts was supported by the differential stretch index, with the teams switching between expansion and contraction in alternating fashion with changes in ball possession . In sum, the space-time patterns of basketball teams, while different with regard to the particular indicators used, were nonetheless consistent with a unified description of self-organizing behaviours in sports competition.